2018
DOI: 10.1049/htl.2018.5072
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality in computer‐assisted interventions based on patient‐specific 3D printed reference

Abstract: Augmented reality (AR) can be an interesting technology for clinical scenarios as an alternative to conventional surgical navigation. However, the registration between augmented data and real-world spaces is a limiting factor. In this study, the authors propose a method based on desktop three-dimensional (3D) printing to create patient-specific tools containing a visual pattern that enables automatic registration. This specific tool fits on the patient only in the location it was designed for, avoiding placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 15 publications
4
53
0
1
Order By: Relevance
“…However, many of the previously mentioned technological developments are based on free and open-source software New Technologies to Improve Surgical Outcome during Open-Cranial Vault Remodeling DOI: http://dx.doi.org /10.5772/intechopen.94536 platforms [12,53], which could reduce the costs associated with its integration on the surgical workflow. Also, CAD/CAM guides and templates can be designed and manufactured in-hospital to reduce cost and production time [60,61]. These technologies could also be shared among different hospital departments, improving their impact at a lower cost.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of the previously mentioned technological developments are based on free and open-source software New Technologies to Improve Surgical Outcome during Open-Cranial Vault Remodeling DOI: http://dx.doi.org /10.5772/intechopen.94536 platforms [12,53], which could reduce the costs associated with its integration on the surgical workflow. Also, CAD/CAM guides and templates can be designed and manufactured in-hospital to reduce cost and production time [60,61]. These technologies could also be shared among different hospital departments, improving their impact at a lower cost.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the literature presents error ranges from 0 to 10 mm by using diverse navigation and accuracy measurement methods on different surgical specialties with the Microsoft HoloLens [8,28,29,[32][33][34]. This collective experimental heterogeneity makes it cumbersome to pinpoint the crucial elements that create such data variability.…”
Section: Discussionmentioning
confidence: 99%
“…The video component of this article can be found at https://www.jove.com/video/60618/ 2 . These methods have been considered somewhat limited when an accurate registration is required 19 . To overcome these limitations, this work provides tools to perform accurate and simple patient-to-image registration in AR procedures by combining AR technology and 3DP.…”
Section: Video Linkmentioning
confidence: 99%
“…Both AR and 3DP technologies help to improve orientation, guidance, and spatial skills in medical procedures; thus, their combination is the next logical step. Previous work has demonstrated that their joint use can increase value in patient education 16 , facilitating explanations of medical conditions and proposed treatment, optimizing surgical workflow 17,18 and improving patient-to-model registration 19 . Although these technologies have grown exponentially in recent years, their adoption by physicians is still limited, since they require extensive knowledge of engineering and software development.…”
Section: Introductionmentioning
confidence: 99%